Membingkai Warisan Budaya Indonesia dan Nilai-Nilai Islam dalam Science Education for Sustainable Development - Muhamad Imaduddin (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
Sustainable development is a development concept that meets the needs of today's generation without compromising the ability of future generations to meet their needs. This paradigm continues to grow and be applied to the educational aspect as well as through the Education for Sustainable Development (ESD) which presents aspects of society, environment and economy with culture as the underlying dimension. This presentation aims to provides an alternative in shifting the science-learning design that links Indonesian culture and Islamic values ​​within the framework of Science Education for Sustainable Development (SESD). The study of library research is used by considering aspects of science study, Islamic values ​​referenced by Qur'an and Hadith, Indonesian cultural diversity, and aspects of sustainable development. Some of Indonesian cultural potentials can be foundation in SESD such as